Robots, artificial intelligence, and service automation in travel, tourism and hospitality - Ivanov, Stanislav; Webster, Craig (Bingley, U.K. : Emerald Publishing Limited, 2019)
Using a combination of theoretical discussion and real-world case studies, this book analyses the use of robotics, artificial intelligence and services automation (RAISA) within the travel, tourism and hospitality industries. Divided into two sections, the book first concentrates on the theoretical aspects surrounding the use of RAISA in travel, tourism and hospitality. Themes explored include: economic fundamentals customer attitudes chatbot adoption service quality Following on from this, the second section concentrates on current and future use of RAISA technologies in specific subsectors of the tourism economy: hotels, restaurants, travel agencies, museums, and events. With an international scope of authorship and focus, the book is a useful reference source for scholars, students, and general readers interested in robotics, artificial intelligence, and automation technologies. Alongside this, the business insights and case studies examined in the book offer practitioners guidance on how these technologies can and will be incorporated into organizations, particularly those in the travel and tourism industry.
Introduction: RAISA in future travel-related industries / Stanislav Ivanov and Craig Webster -- Section 1: Theoretical issues of robots, artificial intelligence and service automation in travel, tourism and hospitality -- 1. Conceptual framework of the use of robots, artificial intelligence and service automation in travel, tourism, and hospitality companies / Stanislav Ivanov and Craig Webster -- 2. Economic fundamentals of the use of robots, artificial intelligence and service automation in travel, tourism and hospitality / Stanislav Ivanov and Craig Webster -- 3. Self-service technologies in the travel, tourism and hospitality sectors - principles and practice / Petranka Kelly, Jennifer Lawlor and Michael Mulvey -- 4. Customer attitudes towards robots in travel, tourism and hospitality - a conceptual framework / Velina Kazandzhieva and Hristina Filipova -- 5. Making sense of robots - consumer discourse on robots in tourism and hospitality service settings / Ulrike Gretzel and Jamie Murphy -- 6. Chatbot adoption in tourism services: a conceptual exploration / Dandison C. Ukpabi, Bilal Aslam and Heikki Karjaluoto -- 7. The impact of robots, artificial intelligence, and service automation on service quality and service experience in hospitality / Nikola Naumov -- 8. Greggg - a scalable high performance, low cost hospitality robot / Sam R. Thangiah, Michael Karavias, Ryan Caldwell, Matthew Wherry, Jessica Seibert, Abdullah Wahbeh, Zachariah Miller and Alexander Gessinger -- Section 2: Application of robots, artificial intelligence and service automation in travel, tourism and hospitality -- 9. Robots, artificial intelligence and service automation in hotels / Georgina Lukanova and Galina Ilieva -- 10. Robots, artificial intelligence and service automation in restaurants / Katerina Berezina, Olena Cifci and Cihan Cobanoglu -- 11. Robots, artificial intelligence and service automation in travel agencies and tourist information centres / Maya Ivanova -- 12. Robots, artificial intelligence and service automation to the core: remastering experiences at museums / Nuria Recuero Virto and Maria Francisca Blasco Lopez -- 13. The role of robots, artificial intelligence and service automation in events / Alfred Ogle and David Lamb.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Technological innovations -- Management; Business enterprises -- Technological innovations; Tourism -- Technological innovations; Hospitality industry -- Technological innovations; Robotics; Automation; Technology & Engineering, Automation; Artificial intelligence